Alterações placentárias associadas à hipertensão arterial em éguas com laminite crônica no terço final da gestação - Santos, Carlos Anselmo dos (2013)
The cardiovascular changes in horses with laminitis are described since the 70's, however few studies have been conducted to demonstrate such changes in pregnant mares with chronic laminitis. The present study aims to evaluate blood pressure, heart rate, serum cortisol levels, gestational age and placental changes of pregnant mares with chronic laminitis and its consequences for fetal morphometry. A prospective longitudinal case-control was conducted in 6 Thoroughbred horse farms in southern Rio Grande do Sul - Brazil. Were used a total of 20 multiparous mares (10 control animals and 10 animals with chronic laminitis). The selected animals were subjected to clinical examination, blood sample collection and blood pressure measurement on alternate days in the last month of pregnancy. Serum levels of cortisol were obtained by chemiluminescence, and blood pressure measurement by indirect method and apparatus for noninvasive oscillometric sphygmomanometer at the base of the tail. Assessment of placental was effected by using the histological method of Schlafer (2004) and morphometric using ImageJ® software. Mean control group regarding measurements of systolic blood pressure were 98,3 ± 1,41 mmHg. The average diastolic blood pressure was 62,2 ± 1,14 mmHg. The mean heart rate was 44 ± 0,53 bpm and the mean serum cortisol levels were 5,06 ± 0,14 μg/dL. The group of pregnant mares with chronic laminitis kept the mean systolic blood pressure and heart rate higher than the control group, being respectively 116 ± 6,73 mmHg and 52 ± 4 bpm. The average values of diastolic blood pressure was 70 ± 7,3 mmHg and mean serum cortisol was 5,07 ± 0,19 μg/dL with no difference compared to the control group. The placentas of pregnant mares with laminitis had higher number of chronic histological changes and higher wall thickness / lumen than the control group (p <0,05). The foals born from mares of the control group had higher birth weight than foals born from chronic laminitis s group mares (p <0,05).